Planned online language education versus crisis‐prompted online language teaching: Lessons for the future - Gacs, Adam; Goertler, Senta; Spasova, Shannon (Foreign language annals, 2020)
Online (language) teaching has been found to be as effective as face‐to‐face (F2F) learning (Moneypenny & Aldrich 2016, J. Educators Online, 13, 105–174; Goertler & Gacs, 2018, Die Unterrichtspraxis/Teaching German, 51, 156–174). Online language teaching has different affordances and challenges than F2F teaching, which can be taken into consideration when online language education is carefully planned using a backwards design iterative process (e.g., Meskill & Anthony, 2015, Teaching language online). In early 2020, many institutions rapidly transitioned away from F2F instruction due to the global pandemic. While this was at times referred to as online teaching, it in fact is not planned online teaching but rather crisis‐prompted remote teaching (Hodges, Moore, Lockee, Trust, & Bond, 2020, Educause Review, 27 March). Given the circumstances and the timeframes for crisis online teaching, quality expectations must be lowered especially in regards to testing security, technological sophistication, accessibility, copyright, and learning outcomes. This article presents a roadmap for planning, implementing, and evaluating online education in ideal and in crisis contexts. The Challenge In Spring 2020, teachers around the globe were suddenly forced to teach online, learners forced to learn online. Emotions ran high, lawsuits were filed. Yet, it is important to acknowledge that this crisis‐prompted remote language teaching is not comparable to well‐designed and carefully planned online language education.